Polypoidal choroidal vasculopathy upon optical Coherence tomographic angiography - Chan, Yann Szy; Jonas, Jost B. (Retina, 2018)
To study polypoidal lesions and branching choroidal vascular networks in eyes with polypoidal choroidal vasculopathy by optical coherence tomography (OCT)-based angiography (OCTA). In the observational cross-sectional study, patients with polypoidal choroidal vasculopathy, as diagnosed by indocyanine green angiography, underwent OCTA. Thirty-two eyes of 31 patients with an age of 61.1 ± 7.6 years were included. Branching choroidal vascular networks were detected by indocyanine green angiography and OCTA in 25 of 32 (78 ± 73%) and in 30 of 32 (94 ± 4%) eyes, respectively, with a marginally significant difference (P = 0.06) in the detection rate between both techniques. A total of 72 polyps (area, 0.06 ± 0.06 mm2; range, 0.01-0.27 mm2) were detected by indocyanine green angiography, and they were consistently present on the OCTA images. By moving the reference level in the OCT angiograms to the corresponding layer, the polypoidal lesions showed cluster-like structures in 53 of 72 polypoidal lesions (74%). In 60 of the 72 polypoidal lesions (83%), cluster-like structures were detected in the en face structural OCT images at the reference plane of the OCTA images. On the cross-sectional OCT images, some internal channels of flow were seen in 50 of the 72 polypoidal lesions (69%). Larger size of the polypoidal lesions was associated with a higher prevalence of cluster-like structures on the OCTA images, some internal channels of flow on the en face structural images, and clustered vascular structures on the cross-sectional OCT images. In conclusion, OCTA is a useful technique for the noninvasive detection of branching choroidal vascular networks including visualization of details such as cluster-like structures and flow. In some eyes, OCTA was superior to indocyanine green angiography to detect polypoidal choroidal vasculopathy and to show branching choroidal vascular networks.